How do anxiety and stress impact the performance of Chinese doctoral students through self-regulated learning?—A multi-group analysis - Li, Zhen; Huang, Jinyan; Hussain, Shahbaz; Shu, Tiantian (Frontiers in Psychology, 2023)
Highly accomplished doctoral students may suffer when they cannot manage their performance due to the crippling effects of anxiety and stress. This is even more likely to occur in the highly charged setting of competitive research.Using a structural equation modeling approach, this study examinedhow anxiety and stress impact the performance of Chinese doctoral students through self-regulated learning. A total of 491 doctoral students and recent completers representing 112 universities in China participated in this study. A 42-item five-point Likert scale survey was used to measure participants’ perceived anxiety (emotional and physical reactions), stress (study- and research-related stress), self-regulated learning, and performance (task and contextual performance) in their doctoral studies.Specifically, the extent to whichparticipants’ self-regulated learning mediated the influence of anxiety and stress on their task performance and contextual performancein their doctoral studies, as well as significant structural equation modeling differences across demographic variables of gender (.i.e., male versus female), major (i.e., arts versus sciences), status (i.e., individuals pursuing a doctoral degree versus recent completers), and age (i.e., 30 and younger versus over 30) were examined.The results indicated that self-regulated learning considerably affected task and contextual performance; stress had a considerable direct effect on task and contextual performance; the indirect influence of stress on task and contextual performance via self-regulated learningwas significant, andthere was a significant structural equation modeling difference between arts and sciences doctoral students. Educational implications are discussed.